A Multilayered Electron Extracting System for Efficient Perovskite Solar Cells - Seitkhan, Akmaral; Neophytou, Marios; Hallani, Rawad K.; Troughton, Joel; Gasparini, Nicola; Faber, Hendrik; Abou‐Hamad, Edy; Hedhili, Mohamed Nejib; Harrison, George T.; Baran, Derya; Tsetseris, Leonidas; Anthopoulos, Thomas D.; et al. (Advanced functional materials, 2020)
Power conversion efficiencies of perovskite solar cells (PSCs) have rapidly increased from 3.8% to a certified 25.2% within only a decade. Eliminating possible recombination losses at the interfaces is essential to further improve both efficiency and stability of this class of emerging photovoltaic technology. Herein, a simple approach for improving the electron extraction of the PC60BM electron transport layer (ETL) is presented by sequentially depositing Al:ZnO (AZO) and triphenyl‐phosphine oxide (TPPO) on top of it, in a p–i–n device configuration. The efficiency of the resulting CH3NH3PbI3‐based solar cell is shown to improve from 14.6%, measured for the control PC60BM‐only cell, to 17.9% for double‐ETL (PC60BM/AZO) and 19.2% for triple‐ETL (PC60BM/AZO/TPPO)‐based devices, respectively. Optimized triple‐ETL‐based cells exhibit high fill factor of 82%. The combination of electrical and quantum mechanical calculations shows that efficiency improvement is attributed to reduced trap‐assisted recombination at the interface and better energy level alignment due to chemical interactions between PC60BM, AZO, and TPPO. Moreover, it is shown that the use of multilayer ETL results in better device stability (T80 ≈ 800 h) under constant illumination. This work opens new possibilities for inexpensive highly efficient and stable multilayered contacts for PSCs by combining organic small molecules and metal oxides. The charge‐extracting properties of PC60BM, the electron transporting layer (ETL) widely used in perovskite solar cells, are greatly enhanced by complementing with Al:ZnO and triphenyl‐phosphine oxide films. Using these triple‐ETL results in a major improvement in device performance in terms of both efficiency and stability, due to better energy alignment, reduced trap‐assisted recombination, and higher built‐in voltage.